Deflation in Islamic Economics: A Solution from the Perspective of Modern Islamic Civilization - Muhammad Nur Alim; Khusnuddin (al-Afkar, Journal For Islamic Studies, 2025)
The phenomenon of deflation, which is characterized by a general decline in prices, is often considered a major challenge in modern economics because it can trigger economic crises, such as economic contraction and unemployment. In Islamic economics, deflation is not only viewed from a technical angle, but also from a moral and ethical perspective based on the principles of justice, balance, and public good. Islam prohibits practices such as usury and hoarding that exacerbate the effects of deflation, while encouraging wealth redistribution through instruments such as zakat, infaq and waqf.This study aims to examine the solution to deflation based on an Islamic economic perspective and its relevance in facing modern economic challenges. Using a literature-based qualitative-descriptive approach, this research explores the concepts of classical thinkers such as Al-Maqrizi and their application in the era of globalization. The results show that the application of Islamic financial instruments, the strengthening of the real sector, and the elimination of usury can create sustainable economic stability. This solution not only focuses on short-term economic recovery, but also promotes equitable and inclusive growth.